A chemosynthetic ecotone—“chemotone”—in the sediments surrounding deep-sea methane seeps - Ashford, Oliver Simon (2021)
Ecotones have been described as “biodiversity hotspots” from myriad environments, yet have not been studied extensively in the deep ocean. While physiologically challenging, deep-water methane seeps host highly productive communities fueled predominantly by chemosynthetic pathways. We hypothesized that the biologi cal and geochemical influence of methane seeps extends into background habitats, resulting in the formation of a “chemotone” where chemosynthesis-based and photosynthesis-based communities overlap. To investigate this, we analyzed the macrofaunal assemblages and geochemical properties of sediments collected from “active,” “transition” (potential chemotone), and “background” habitats surrounding five Costa Rican methane seeps (depth range 377–1908 m). Sediment geochemistry demonstrated a clear distinction between active and transi tion habitats, but not between transition and background habitats. In contrast, biological variables confirmed the presence of a chemotone, characterized by intermediate biomass, a distinct species composition (including habitat endemics and species from both active and background habitats), and enhanced variability in species composition among samples. However, chemotone assemblages were not distinct from active and/or back ground assemblages in terms of faunal density, biological trait composition, or diversity. Biomass and faunal sta ble isotope data suggest that chemotones are driven by a gradient in food delivery, receiving supplements from chemosynthetic production in addition to available photosynthetic-based resources. Sediment geochemistry suggests that chemosynthetic food supplements are delivered across the chemotone at least in part through the water column, as opposed to reflecting exclusively in situ chemosynthetic production in sediments. Manage ment efforts should be cognisant of the ecological attributes and spatial extent of the chemotone that surrounds deep-sea chemosynthetic environments.